DEGRADASI SENYAWA PERMETRINDENGAN MENGGUNAKAN TiO2-Anatase DAN ZEOLIT ALAM SECARA SONOLISIS - -, Zilfa; Suyani, Hamzar; -, Safni; Jamarun, Novesar (Universitas Andalas, 2009)
ABSTRACT The research about the degradation of permethryn compound had been done by sonolysis method using anatase- TiO2 and natural zeolyte (mordenit kinds) as catalysts. Permethryn is one of synthetic pyretroid pesticides that low toxicity for mamals but it is high toxicity for fishs, insects and water microorganisms. Sonolysis method is conducted by using ultrasonic wave at frequency 45 kHz. The results show that sonolysis method without the addition of anatase-TiO2 and zeolite on optimum temperature at 40°C during 120 minutes treatments could be degrade 20 mg/L permethryn until 22.23%. In other hands, the degradation of 20 mg/L permethryn in the same condition with adding 0.002 g anatase-TiO2 achieved 44.95% but for using 0.2 g zeolyte could be degrade 52.34%. Keywords : degradation, permethrin ,TiO2-anatase , sonolysis, zeolite